Chaos-enhanced manganese electrolysis: nodule suppression and improved efficiency using controllable chaotic electrical signals - Jie Yang; Chunbiao Li; Qian Zhang; Zhihao Wu; Xin Zhang; Peiqiao Liu; Zuohua Liu; Changyuan Tao; Guocan Zheng; Yong Yang; Hanke Wei (Scientific Reports)
Abstract The control and industrial application of chaotic systems is a major obstacle limiting the diffusion of chaos theory. In this study, we proposed a novel, universally applicable methodology for constructing an offset boosting function for chaotic systems. By integrating this approach with traditional techniques, a four-dimensional chaotic system with two-dimensional offset boosting was developed and successfully implemented by a real chaotic circuit for manganese metal electrolysis, replacing conventional DC. It has been shown that the use of time-varying electricity facilitates the suppression of electrochemical oscillations, and inhibits the growth of spherical manganese nodules. An examination of current efficiency for different oscillations (period 1, period 2, chaos-a and chaos-b) and various current amplitudes has established that chaos-a electrical signals are most suitable for inhibiting the growth of manganese nodules. The Mn nodule area ratios can be reduced by 38% with a 5.83% increase in current efficiency, representing an energy consumption saving of 0.58 kWh/kg. This interdisciplinary approach holds promise for advancing the study of nonlinear dynamic behavior in electrochemical reaction processes and addressing critical challenges in various fields, such as energy dissipation, quality improvement of electrodeposited products, and regulation of by-product properties.